Transferring Transnationally, Transforming Locally, Imagining Transnationally: The Transference of Interwar Poland’s Popular Culture to Israel and Its Rediscovery in the Last Decades - Marcos Silber (Postscriptum Polonistyczne)
The article addresses the relationship of Jewish audiences in Mandatory Palestine/Israel to the cultural heritage of the Second Polish Republic, examining the transfer of Polish interwar popular culture to Palestine during the mandate period and to Israel after 1948, as well as the contemporary revival of interest in this cultural phenomenon. The author analyzes various levels and forms of cultural transfer, considering the roles of artistic communities and audiences, individual initiatives and institutional infrastructure, and social and economic factors. The study also comments on the transformations of cultural texts undergoing transfer, which are adapted to meet new audience needs and reshaped by functioning within novel cultural contexts. The theoretical framework is constructed using categories of transfer, transnationality, locality, adaptation, identity, cosmopolitanism, translation, and contact zone. The transfer of Polish popular culture occurs through diverse cultural practices, with translation playing a pivotal role. This transfer takes place in a transgeographic contact zone defined by the relational space between Warsaw and Tel Aviv as centres of modern culture. In contemporary Israel, references to interwar Polish popular culture and its local adaptations serve a subversive and critical function in relation to the state’s identity politics.